Paying attention to gender and poverty in health research: content and process issues - Piroska Östlin; Gita Sen; Asha George (The World Health Organization, 2004)
Despite the magnitude of the problem of health inequity within and between countries, little systematic research has been done on the social causes of ill-health. Health researchers have overwhelmingly focused on biomedical research at the level of individuals. Investigations into the health of groups and the determinants of health inequities that lie outside the control of the individual have received a much smaller share of research resources. Ignoring factors such as socioeconomic class, race and gender leads to biases in both the content and process of research. We use two such factors - poverty and gender - to illustrate how this occurs. There is a systematic imbalance in medical journals: research into diseases that predominate in the poorest regions of the world is less likely to be published. In addition, the slow recognition of women's health problems, misdirected and partial approaches to understanding women's and men's health, and the dearth of information on how gender interacts with other social determinants continue to limit the content of health research. In the research community these imbalances in content are linked to biases against researchers from poorer regions and women. Researchers from high-income countries benefit from better funding and infrastructure. Their publications dominate journals and citations, and these researchers also dominate advisory boards. The way to move forward is to correct biases against poverty and gender in research content and processes and provide increased funding and better career incentives to support equity-linked research. Journals need to address equity concerns in their published content and in the publishing process. Efforts to broaden access to research information need to be well resourced, publicized and expanded.